2020
DOI: 10.1002/cncr.32667
|View full text |Cite
|
Sign up to set email alerts
|

Extracapsular extension of neck nodes and absence of human papillomavirus 16‐DNA are predictors of impaired survival in p16‐positive oropharyngeal squamous cell carcinoma

Abstract: BACKGROUND: Human papillomavirus (HPV)-driven oropharyngeal squamous cell carcinomas (OPSCCs) demonstrate superior outcome compared with HPV-negative OPSCCs. The eighth edition of the American Joint Committee on Cancer/Union for International Cancer Control (AJCC/UICC) tumor, lymph node, metastasis (TNM) classification (TNM 2017) modifies OPSCC staging based on p16 positivity as a surrogate for HPV-driven disease. In p16-negative OPSCCs, lymph node (N) categories include extracapsular/extranodal extension (ECE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 47 publications
2
42
0
4
Order By: Relevance
“…Besides improved outcome in the oropharyngeal cancers presenting initially as NSCCUP (data not shown), we provide evidence that a standardized diagnostic workup followed by riskadapted treatment described improves the outcome even in definitive NSCCUP-P without detection of primary lesions (Table 1 and Figures 2-5). The evidence-based decisionmaking for further diagnostic and the standardized treatment planning for CRT, Op + PORT or risk-adapted cisplatin-based Op + PORCT improve outcome as demonstrated in oropharyngeal cancer (29). The diagnostic step carrying a substantial therapeutic effect improving survival was ND.…”
Section: Discussionmentioning
confidence: 99%
“…Besides improved outcome in the oropharyngeal cancers presenting initially as NSCCUP (data not shown), we provide evidence that a standardized diagnostic workup followed by riskadapted treatment described improves the outcome even in definitive NSCCUP-P without detection of primary lesions (Table 1 and Figures 2-5). The evidence-based decisionmaking for further diagnostic and the standardized treatment planning for CRT, Op + PORT or risk-adapted cisplatin-based Op + PORCT improve outcome as demonstrated in oropharyngeal cancer (29). The diagnostic step carrying a substantial therapeutic effect improving survival was ND.…”
Section: Discussionmentioning
confidence: 99%
“…Among other things, they showed that microscopic or macroscopic ENE results in a significantly worse OS when compared to positive lymph nodes without ENE (5J-OS: 91% vs. 78%; p < 0.0001) ( 43 ). In addition, Freitag et al recently published their analysis of a cohort of 92 patients with surgically treated HPV-mediated OPSCC (IC+OP+RT: n = 8, OP: n = 21, OP+RT: n = 23, OP+RCT: n = 39, OP+RT+Cetuximab: n = 1) ( 44 ). Their multivariate analysis showed that ENE represents an independent predictor for decreased OS ( p = 0.033), tumor-specific survival ( p = 0.165), progression-free survival ( p = 0.42), and DFS ( p = 0.04) ( 44 ).…”
Section: Extranodal Extension In the Context Of The 8th Uicc Classifimentioning
confidence: 99%
“…In addition, Freitag et al recently published their analysis of a cohort of 92 patients with surgically treated HPV-mediated OPSCC (IC+OP+RT: n = 8, OP: n = 21, OP+RT: n = 23, OP+RCT: n = 39, OP+RT+Cetuximab: n = 1) ( 44 ). Their multivariate analysis showed that ENE represents an independent predictor for decreased OS ( p = 0.033), tumor-specific survival ( p = 0.165), progression-free survival ( p = 0.42), and DFS ( p = 0.04) ( 44 ). The results of their investigation as a whole led them to the conclusion that ENE (as well as HPV16 DNA status) should be integrated in the prognostic staging algorithm of HPV-mediated OPSCC ( 44 ).…”
Section: Extranodal Extension In the Context Of The 8th Uicc Classifimentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of LNMs bears a major prognostic influence, with an estimated 50% reduction in overall survival in nodal negative vs. nodal positive HPV-negative HNSCC [ 6 , 7 , 8 ]. Features such as number, size, location in the neck, and the presence of extracapsular extension (ECE) among others equally have a negative impact on survival and oncological outcome [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%